Analysis of the Effect of Organizational Climate, Work Motivation, and Job Satisfaction on Lecturer Performance at Medan State Polytechnic - Hartono Ginting; Martolop Sinambela; Pirma Sibarani; Jamardua Haro; Jasa Ginting (CV. Syntax Corporation Indonesia, 2022)
The human qualities needed by the Indonesian nation in the future are humans who are able to compete with other countries. Obtaining quality human beings will be produced through the implementation of quality education. This study aims to determine the effect of organizational climate, work motivation and job satisfaction on the performance of lecturers at the Medan State Polytechnic. The population includes all lecturers who have civil servant status, totaling 310 people with a sample of 76 people taken by proportionate random sampling. Data was collected by using interview techniques, questionnaires and documentation studies. The data analysis technique uses Multiple Regression analysis so that it can be seen the influence of organizational climate, work motivation and job satisfaction on lecturer performance either partially or simultaneously. The results of the research show that simultaneously organizational climate, work motivation and job satisfaction have a positive and significant effect on lecturer performance. Partially, organizational climate and work motivation have a positive and significant effect on lecturer performance, while job satisfaction has a positive and insignificant effect on lecturer performance.